Perceived Implementation of Enhanced Basic Education Information System-Learners Information System (EBEIS-LIS): The Case of Elementary Teachers in Eastern Samar, Philippines - Denver J. Balaclaot (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2021)
This study assessed the implementation of the Enhanced Basic Education Information System-Learners Information System (EBEIS-LIS) in the San Julian district, province of Eastern Samar during the school year 2020-2021.  The data concerning teachers’ perceived extent of EBEIS-LIS implementation were collected via a validated researcher-made survey instrument and was analyzed usingmedian. Findings revealed that most of the respondents perceived a high extent of EBEIS-LIS implementation in terms of manpower requirement, methods of employment, and materials for implementation. Hence, the researcher recommends the conduct of an extensive training program appropriate to teachers’ teaching experience especially in handling their respective school’s information system.